2014
DOI: 10.1093/ijnp/pyu043
|View full text |Cite|
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Axis Dysfunction and Illness Progression in Bipolar Disorder

Abstract: Background:Impaired stress resilience and a dysfunctional hypothalamic-pituitary-adrenal (HPA) axis are suggested to play key roles in the pathophysiology of illness progression in bipolar disorder (BD), but the mechanisms leading to this dysfunction have never been elucidated. This study aimed to examine HPA axis activity and underlying molecular mechanisms in patients with BD and unaffected siblings of BD patients.Methods:Twenty-four euthymic patients with BD, 18 siblings of BD patients, and 26 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 45 publications
6
56
0
2
Order By: Relevance
“…Previous reports have linked stress sensitivity to the pathophysiology of schizophrenia [i.e., blunted hypothalamic-pituitary-adrenal (HPA) axis corticosterone response] using animal models (Zimmerman et al, 2013), along with reduced hippocampal volume serving as a marker of stress sensitivity in psychotic disorders (Collip et al, 2013). Similar findings have been observed in bipolar disorders, such as reduced cortisol metabolism (Steen et al, 2014; Steen et al, 2011) and glucocorticoid receptor hyporesponsiveness (Fries et al, 2014). Stress sensitivity via HPA axis function may also play a role in the development of psychotic symptoms in at-risk populations (Corcoran et al, 2012) and has been implicated in the onset of bipolar spectrum disorders (Alloy et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…Previous reports have linked stress sensitivity to the pathophysiology of schizophrenia [i.e., blunted hypothalamic-pituitary-adrenal (HPA) axis corticosterone response] using animal models (Zimmerman et al, 2013), along with reduced hippocampal volume serving as a marker of stress sensitivity in psychotic disorders (Collip et al, 2013). Similar findings have been observed in bipolar disorders, such as reduced cortisol metabolism (Steen et al, 2014; Steen et al, 2011) and glucocorticoid receptor hyporesponsiveness (Fries et al, 2014). Stress sensitivity via HPA axis function may also play a role in the development of psychotic symptoms in at-risk populations (Corcoran et al, 2012) and has been implicated in the onset of bipolar spectrum disorders (Alloy et al, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…13 Accordingly, chronically stressed individuals have shown lower telomerase activity, 13 and ex vivo exposure of lymphocytes to cortisol has been shown to reduce telomerase activity. 34 HPA axis impairment has been found in patients with BD, 7,35 as demonstrated by increased cortisol levels 36 and cortisol non-suppression in the dexamethasone suppression test. 37 Increased stress exposure and cortisol levels might thus accelerate telomere shortening.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms might be implicated in telomere shortening in BD, including oxidative stress 28 leading to secondary DNA damage, 29 inflammation, 30 and glucocorticoid load. 7 Mechanistically, oxidative stress can lead to the formation of 8-oxo-7,8-dihydro-2 0 -deoxyguanosine (8-oxodG) at the GGG triplet in telomere sequences, 31 which is noted to be increased in patients with BD. 32 Chronic systemic inflammation has also been shown to accelerate aging via reactive oxygen species-mediated exacerbation of telomere dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been demonstrated that depressed, bipolar and SKZ patients present higher baseline cortisol in plasma and cerebrospinal fluid than healthy controls, as well as an increased secretion of adrenocorticotropic hormone and of cortisol after dexamethasone suppression tests [5,6], although data in the literature are not completely concordant [7,8]. Among patients with bipolar disorder (BD), most of these changes are present in both depressive and manic episodes and during euthymia, suggesting a chronic dysfunction of the hypothalamic-pituitary-adrenal axis [6,9]. …”
Section: Introductionmentioning
confidence: 99%